Removal of Self-Expanding Metallic Stents. Issue 4 (October 2016) - Shah, Shiwan K.; Jennings, Jeffrey H.; Diaz-Mendoza, Javier I.; Yessayan, Lenar; Ray, Cynthia; Simoff, Michael J.
Abstract : Background: Despite their safety profile, self-expanding metallic stents (SEMS) have been difficult to remove. We aim to describe our experience in removal of SEMS at Henry Ford Hospital with a specific emphasis on safety. Methods: We reviewed the charts of all patients who underwent removal of a SEMS at Henry Ford Hospital between 2003 and 2013. We recorded demographic information, indication for initial stent placement, indication for stent removal, time to stent removal, procedure of removal, and any complications. Results: In all, 19 stents were removed in 16 separate procedures in 14 patients. The median age was 62 years, and 50% of the patients were female. Stents were removed at a median of 35 days (range, 2 to 595 d). No complications occurred in 10/16 (62.5%) procedures. In the remaining 5 patients, complications were not directly related to the stent removal, and serious complications were mostly related to severity of underlying lung disease. Of the 10 procedures done as outpatients, 70% were discharged immediately after the procedure. Conclusions: Removal of SEMS can be done safely. Routine postoperative ventilation and intensive care unit monitoring is not required. In the absence of severe underlying lung disease, patients can safely be discharged if there are no immediate postprocedure complications.